Perlindungan Pekerja Anak Menurut Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan di Pasar Kasih Naikoten 1 Kupang (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to analyse the protection of child labour according to Law No. 13 of 2003 concerning labour in Pasar Kasih Naikoten 1 Kupang This research is an empirical legal research conducted in Pasar Kasih Naikoten 1 Kupang City, the Office of Manpower and Transmigration of Kupang City and the Office of Empowerment and Child Protection of Kupang City. This research uses primary data and secondary data. Data collection techniques using interviews, documents, observation. Based on the results of research and discussion, the conclusion is that there are still many children who work under the age of 18 and do heavy work such as pushing trains, lifting shopping that exceeds the capacity of children, even among those who get physical and verbal violence from people around them. If there is a violation of child labour in the Kasih Naikoten 1 market, the relevant government will issue a written warning and if there is a criminal act, the government will provide legal assistance to victims and perpetrators and will be processed by the applicable law. Factors that hinder the government to tackle the problem of child labour are very small APBD, economic factors, cultural factors and educational factors.